Exogenous salicylic acid treatments enhance tolerance to salinity of wheat (Triticum aestivum) plantlets - Purcǎrea, Cornelia; Cachită, Dorina; Petrus, Adriana; Pop, Liviu; Chis, Adriana (Acta Agraria Debreceniensis, 2010)
Salt stress, an abiotic stress, determines modifications of some biochemical indicators, like, antioxidant enzymes, proline (amino acidaccumulate in higher plants under salinity stress) content, and some physiological processes including: plant growth and development. Inthis paper we studied the influence of exogenous treatment of wheat seeds, with 0.1 mM salicylic acid (SA) solution, in the plant response tosalt stress. The treatment was applied by presoaking the seeds in the treatment solution for 12 hours before germination. The results showedthat exogenous 0.1 mM SA solution, administrated to the wheat cariopses significantly ameliorated the negative effect of salt stress in firstweek of germination in laboratory conditions.